2001
DOI: 10.1104/pp.126.1.388
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Measure Gross CO2 Fluxes in Leaves. Gross CO2 Assimilation, Photorespiration, and Mitochondrial Respiration in the Light in Tomato under Drought Stress

Abstract: We developed a new method using 13 CO 2 and mass spectrometry to elucidate the role of photorespiration as an alternative electron dissipating pathway under drought stress. This was achieved by experimentally distinguishing between the CO 2 fluxes into and out of the leaf. The method allows us to determine the rates of gross CO 2 assimilation and gross CO 2 evolution in addition to net CO 2 uptake by attached leaves during steady-state photosynthesis. Furthermore, a comparison between measurements under photor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 26 publications
1
98
3
Order By: Relevance
“…There is less consensus in the literature of how drought impacts respiration rate (Atkin and Macherel, 2009). In some cases, drought was reported to have little or no effect on respiration rate (Ribas-Carbo et al, 2005;Giraud et al, 2008;Gimeno et al, 2010), whereas other studies reported decreases (Haupt-Herting et al, 2001;Haupt-Herting and Fock, 2002;Taylor et al, 2005;Vassileva et al, 2009;Galle et al, 2010;Ayub et al, 2011) or even increases (Bartoli et al, 2005;Feng et al, 2008;Hummel et al, 2010;Begcy et al, 2011). We found that both R D and R L tended to be lower (by about 27%) in moderate drought-stressed than well-watered wild-type N. tabacum (Fig.…”
Section: Knockdown Of Aox Restricts Respiration Rate During Moderate mentioning
confidence: 84%
“…There is less consensus in the literature of how drought impacts respiration rate (Atkin and Macherel, 2009). In some cases, drought was reported to have little or no effect on respiration rate (Ribas-Carbo et al, 2005;Giraud et al, 2008;Gimeno et al, 2010), whereas other studies reported decreases (Haupt-Herting et al, 2001;Haupt-Herting and Fock, 2002;Taylor et al, 2005;Vassileva et al, 2009;Galle et al, 2010;Ayub et al, 2011) or even increases (Bartoli et al, 2005;Feng et al, 2008;Hummel et al, 2010;Begcy et al, 2011). We found that both R D and R L tended to be lower (by about 27%) in moderate drought-stressed than well-watered wild-type N. tabacum (Fig.…”
Section: Knockdown Of Aox Restricts Respiration Rate During Moderate mentioning
confidence: 84%
“…The rates of net O 2 uptake, which are nearly identical to net CO 2 release, are comprised of O 2 evolution in the Hill reaction of PS II, O 2 consumption by the Mehler reaction and the glycolytic pathway, and O 2 consumption in mitochondrial respiration in the light, whereas photorespiratory CO 2 evolution is accompanied by CO 2 uptake in the Calvin cycle and CO 2 release from mitochondrial respiration (61). Based on these facts and the photosynthetic properties of the OsCHLH mutant it is possible that respiration in the light may depend on the amount of photosynthetic primary products (61,62), which the mutants are expected to lack because there is no photosynthetic CO 2 fixation. This could explain, as it does in drought-stressed plants (61) the substantial decrease of mitochondrial O 2 uptake and CO 2 release in the OsCHLH mutant in the light.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, even if photorespiration had been increased during the period of low g, it should be expected to return to control values following re-watering and concomitant stomatal reopening. As to mitochondrial respiration in the light, Haupt-Herting et al (2001) reported that this process is inhibited by water stress in tomato plants, but to our knowledge, dark respiration in re-watered plants has not been assessed so far. However, increased demand for maintenance respiration may be expected during re-watering, in order to support the repair of dehydration-induced damages, including oxidative damage to lipid, as apparently happened in the present experiments, taking into account the observed increase in foliar levels of MDA (Fig.…”
Section: Influence Of Shading On the Effects Of Soil Drying And Subsementioning
confidence: 96%